Analytic and Heuristic Methodologies for Solving the Resource Constrained Project Scheduling Problem (RCPSP): a Review. Part 2 (2014)
This paper exposes and details the most relevant methods for the solution of the Resource Constrained Project Scheduling Problem, RCPSP. A critical review of the state of the art, based on the most significant papers published in the academic literature o